Clast rind analysis using multi‐high resolution instrumentation. Issue 3 (14th August 2015) - Mahaney, W. C.; Krinsley, D. H.; Razink, Josh; Fischer, Robert; Langworthy, Kurt
Summary: Clast weathering rinds, formed over varying lengths of time (10 2 –10 6 years) in terrestrial environments, are measured to provide relative ages for deposits in glacial sequences, specifically to differentiate between glaciations, occasionally within glaciations. Other studies have sought to reveal weathering rates in non‐glacial environments using microscopic techniques and isotopes. Recent analyses of clast rinds from tropical, mid‐latitude and polar areas reveal an astounding corpus of organic and inorganic paleoenvironmental data derived from atmospheric and biospheric elements active in weathering clasts in glacial deposits over varying lengths of time. In some cases, extreme biochemical products, observed within the rind matrix, are seen to play a role in adjusting redox potentials important in the production of oxides and hydroxides and biominerals with variable compositions. Up to recently, rind analysis has been limited to use of the light microscope and SEM/EDS, which has greatly advanced our understanding of compositional inter‐linkages of minerals and biotic elements, but only along horizontal axes within the rind. A test involving rind surface composition using vertical axis nanospaced layer analysis within rinds using focused ion beam (FIB) and TEM/STEM/EDX imagery and chemistry illustrates the power of data acquisition within the three‐dimensional weathered archive. SCANNING 38:202–212, 2016. © 2015 Wiley Periodicals, Inc.